Transformasi elemen-elemen arsitektur dan interior pada Uma Mentawai: studi kasus desa Matotonan, Kec. Siberut Selatan - Eljihadi Alfin; Widihardjo . (Fakultas Seni Rupa dan Desain ITB, 2020)
When we look at the old Uma Mentawai (communal houses of Mentawai tribe) from various literatures, there is a significant difference with Uma's current condition. This distinction raises an indication of a shift resulting in the transformation of architectural and interior elements. This research is intended to obtain data and information to know, answer, and explain about the transformation of architectural and interior elements in Uma Mentawai. This research belongs to case and field research that belong to social research in architecture and interior design study with qualitative approach. Data collection techniques that the author uses is a mixed method, which combine several techniques. Among them are field observation, literature review, interview, internet exploration, and Focus Group Discussion. After a comparative analysis of the old Uma, Uma's current condition was undergoing some changes to the architecture and interior elements. The elements are: 1) Changes of floor plan, 2) Addition of the bench, 3) Use of board on the wall, 4) The addition of the handle on the stairs, and 5) Use of